INFLUENCE OF RELATIONSHIP MARKETINGAND QUALITY OF SERVICE TOWARDS CUSTOMER LOYALTY WITH MODERATION OF RELIGIUS IN SYARIAH HOTELS (STUDY AT THE GRAND DREAM CITA MANDIRI SYARIAH HOTEL, BATU CITY, EAST JAVA) - Idris, Dany Luqyana; Asnawi, Nur; Rahayu, Yayuk Sri (Indonesian Scientific Journal of Islamic Finance, 2024)
The sharia hotel concept continues to develop in Indonesia, although its growth cannot yet compete with conventional hotels. Providing accommodation in tourism in the form of lodging facilities such as hotels, homestays, etc. Batu City is one of the tourism destinations in Indonesia which is very popular with both domestic and international tourists with various attractions in terms of geography, climate, traditions and arts and culture. This is proven by the continued development of sharia hotels in Indonesia, although the growth cannot yet compete with conventional hotels. Therefore, Syariah Hotels need to retain existing customers and build long-term relationships so that they can bring profits to them. This research aims to determine the direct influence of relationship marketing and service quality on customer loyalty with religiosity as moderation in sharia hotels. The research method used is a quantitative method with an explanatory research approach which functions to prove the contribution of exogenous to endogenous variables. The population in this study were customers of the Grand Dream Cita Mandiri Syariah Hotel, Batu City, East Java. Meanwhile, the sampling technique used purposive sampling technique with specified criteria so that the sample size was 150 respondents. The type of data in this research is primary data obtained through distributing questionnaires to 150 respondents. The data that has been collected is then analyzed using SmartPLS 3.3 software. The research results show that commitment and service quality influence loyalty, while communication has no influence on loyalty. Meanwhile, religiosity is not able to moderate commitment and communication on loyalty, while religiosity is able to moderate service quality on loyalty